Alternative Dispute Resolution (As-Sulh) as a Principle of Islamic Legal System on Marriage Conflicts Among Muslim Ummah - Adamu Abubakar Muhammad; Ibrahim Dahiru Idriss; Adam Muhammad Ardo; Bashir Liman Mashema; Huma Khan (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2023)
This paper seeks to analyze the application of ADR (As-Sulh) as a principle of the Islamic legal system on marriage disputes among Muslim Ummah and the role of Tafarkin Tsira Islamic Centre Azare Bauchi State Nigeria. The paper will examine the principle of As-Sulh for dispute resolution among Muslim Ummah and its applicability in settling marriage disputes in the study area. This study employed qualitative research methods, and the data were gathered through the review of the related literature and interviews with pertinent bodies. The findings revealed that marital conflict among Muslim Ummah is becoming rampant and tends to increase annually. This study also identified that Tafarkin Tsira Islamic Centre Azare, under its Matrimonial Life Training and Counseling section, maintained the principle of ADR (As-Sulh) as a reliable alternative and instrument for the resolution of many marital conflicts among Muslim Ummah in the study area through organizing a strong orientation program for intending and married couples on successful marriages, the consequences of marital disharmony, and how to resolve the issues. It is recommended that ADR, if properly maintained and its technicalities applied, several marriages would be saved, peace would be restored, and collective effort to build successful families would be actualized across the communities.